HUBUNGAN ANTARA POSTUR NATURAL KEPALA DAN KEBERJEJALAN GIGI DEPAN RAHANG BAWAH (Kajian pada fotografi dan model studi pada mahasiswa FKG UGM suku Jawa) - , ANNISA NURUL FIKRI, drg. Wayan Ardhana, MS., Sp. Ort. (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Natural head posture (NHP) is the posture of the head when a person in a standing position with eyes focused on a distant point at the eye level. Head posture is one factor that could affect the occurrence of crowding in dental arch. The most common crowding is in anterior teeth. The aim of this research was to determine the relationship between natural head posture and lower anterior dental crowding in Javanese people. The subjects were 30 students (15 female and 15 male) Faculty of Dentistry, University of Gadjah Mada with criteria : Javanese ethnic (at least two previous generations), age 18-25 years, complete permanent dentition except the third molar, without previous orthodontic treatment, do not have bad habits (thumb sucking, nail/pencil/lip biting, resting chin in the hand, mouth breathing), and willing to be the subject of this research. Each subjects was taken a lateral head profile photo by using camera and was casted the lower dental arch. The images were analyzed using the program coreldraw graphics suite x5 and the study model was assessed by Little's Irregularity Index (LII). Furthermore, the data were analyzed with Pearson parametric correlation test/product moment test (p <0.05). The result of this reaserch indicates a strong correlation between two variables, is that natural head posture and lower anterior dental crowding. The conclusion is there is a positive correlation between natural head posture and lower anterior dental crowding in Javanese people.